SURGICAL MANAGEMENT OF A LARGE MANDIBULAR CYST: A CASE REPORT - Cherana Gioga; Andreea-Mariana Bănățeanu; Ruxandra-Nicolette Voinea-Georgescu; Anca-Monica Dobrescu (Romanian Journal of Oral Rehabilitation, 2024)
Large mandibular cysts have a series of complications including significant anatomical lesions such as bone destruction or maxillofacial deformity. Therefore, the effectiveness of simple conventional curettage of the cyst is not satisfactory. The aim of this study was to investigate several factors that can lead to a successful treatment planning such as an accurate 3D radiological evaluation by using CBCT, the importance of a correct microscopical root canal treatment and filling and the importance of using the A-PRF membrane after the primary enucleation of cysts and the filling of bone defect. Case report A 38-year-old patient presents with pain during mastication and swelling in the anterior mandibula. OPC and CT examination revealed a cystic lesion extending from the mesial of 3.4 to the mesial of 4.3. The endodontic retreatment of the four incisions and lower left canine was performed preoperatory, followed by piezo surgical complete cystic membrane enucleation under local anesthesia and intra-venous sedation. After the endodontic retreatment of 3.2, 3.1, 4.1 and 4.2 due to the large size of the bone defect, A-PRF membrane was used to improve healing of bonny defect. In this case it was used the Duoquattro* centrifuge. The patient was recalled every 1, 3, 6 months for routine intraoral examination. One year later, the CT evaluation revealed bone regeneration. Conclusions The treatment choice for a large mandibular cyst was represented by entirely enucleation of the cyst with intraoral approach using piezo surgical technology. The use of A-PRF membrane is an efficient adjuvant to surgical procedure witch improved bone remodeling and tissue healing, with no post-operative complications. One year later, the CT evaluation revealed bone regeneration.